THE IMPLICATURE OF TEMBANG GAMBUH IN SERAT WEDHATAMA AND ITS SIGNIFICANCE FOR THE SOCIETY - Edy Try Sulistyo (Humaniora, 2015)
This study was aimed to discover the meanings implied in the texts of Tembang Gambuh written by KGPAA Mangkunagara IV in his Serat Wedhatama as well as its significance for the society. The texts were originally composed of 25 stanzas, but this study was limited to those associated with sembah (worship). This study employed qualitative paradigm which was conducted by using an embedded-case-study research design. Data was collected from informants, places and events as well as documents/archives or library sources. The validity of the data was tested using the data triangulation. The data was then analyzed by using a model of pragmatic analysis. The findings based on the pragmatic analysis suggested that the dominant implicatures in the Tembang Gambuh in relation to sembah were sembah raga (worship by physical conduct), sembah cipta (worship by controlled/mind conduct), sembah jiwa (spiritual/soul worship), and sembah rasa (worship beyond rituals). For the society, these four types of worship can serve as a warning and moral education that have significant values for someone to draw closer to God by performing worship in accordance to the guideline.